The Impact of Export and Foreign Direct Investments on Macedonian GDP Growth - Empirical Analysis - Shaqiri, Jeton (European Scientific Journal, ESJ, 2017)
In this paper in chronological order is analyzed the Macedonia's economic development in general, considering that the country has a liberal trade regime which is characterized by simplicity and neutrality. R. of Macedonia should utilize this trade regime in direction of creating policies and conditions for promoting the private sector development and its possibilities for export that will contribute for greater macroeconomic development. The paper will have a detailed look to the overall economic development and the GDP growth, the components and the main factors influencing this growth, techniques and approaches of assessment of the economic system and its development. It will also analyze the role of exports and the foreign direct investments in Macedonian GDP growth. Numerous theoretical researches related to the role of exports and FDI in GDP growth, have shown a positive relationship between them. The data used in this paper were provided by the Statistical Office of Macedonia and the Macedonian Customs in different periods, while for the empirical analysis I have included the period from 2014-2015. Within the empirical analysis is applied a model of multiple linear regression, where is defined the dependent variable "GDP growth" as well as the independent variables: the growth of FDI and the growth of export.